Two new dwarfgobies from the Southwestern Pacific Ocean (Teleostei: Gobiidae: Eviota) - Greenfield, David W.; Winterbottom, Richard (Zootaxa, 2012)
Two species of Eviota with red or orange bars crossing the body, a bifurcated 4th pelvic-fin ray with two long branches,and lacking many or all cephalic sensory-canal pores are described from Palau, Indonesia, and Papua New Guinea. Eviotajewettae has a dorsal/anal fin-ray formula of 8/8, 98% of the specimens lack all cephalic sensory-canal pores, 2–4 lowerpectoral-fin rays branched; non-filamentous dorsal-fin spines; short tubular anterior nares that are not black and are lessthan ½ pupil diameter in length, and five wide bars across the body. Eviota pinocchioi has a dorsal/anal fin-ray formulaof 9/8, always lacks the POP and IT pores and the PITO and AITO pores are fused in about 50% of the specimens, un-branched pectoral-fin rays, males with filamentous dorsal-fin spines, tubular anterior nares black and very long, almost equal to the pupil diameter, and six narrow bars across body.